Stonewall of the West : Patrick Cleburne and the Civil War - Symonds, Craig L. (Lawrence, Kan. : University Press of Kansas, 1997)
To Jefferson Davis, he was the "Stonewall of the West"; to Robert E. Lee he was "a meteor shining from a clouded sky"; and to Braxton Bragg, he was an officer "ever alive to a success." He was Patrick Ronayne Cleburne, one of the greatest of all Confederate field commanders. In Stonewall of the West, Craig Symonds offers the first full-scale critical biography of this compelling figure. He explores all the sources of Cleburne's commitment to the Southern cause, his.
growth as a combat leader from Shiloh to Chickamauga, and his emergence as one of the Confederacy's most effective field commanders at Missionary Ridge, Ringgold Gap, and Pickett's Mill. In addition, Symonds unravels the "mystery" of Spring Hill and recounts Cleburne's dramatic and untimely death (at the age of 36) at Franklin, Tennessee, where he charged the enemy line on foot after having had two horses shot from under him. Symonds also explores Cleburne's role in the.
complicated personal politics of the Army of Tennessee, as well as his astonishing proposal that the decimated Confederate ranks be filled by ending a slavery and arming blacks against the Union.
Pat Cleburne's Ireland -- Helena, Arkansas -- Command -- First blood: Shiloh -- The Kentucky Campaign -- Cleburne's division -- War and politics -- Barren victory: the Battle of Chickamauga -- Stonewall of the west -- "A plan which we believe will save our country" -- From Dalton to the Chattahoochee -- The battles for Atlanta -- The last crusade.
Includes bibliographical references (p. 303-314) and index.
Keywords: Cleburne, Patrick Ronayne, -- 1828-1864.; Generals -- Confederate States of America -- Biography; Confederate States of America. -- Army -- Biography; United States -- History -- Civil War, 1861-1865 -- Campaigns; Georgia -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; Helena (Ark.) -- Biography